A Fuzzy Logic Model for the Analysis of Social Corporate Responsibility - Golzio, A. C.; Puerta-Díaz, M.; Martínez-Ávila, D. (EAI Endorsed Transactions on Scalable Information Systems, 2021)
INTRODUCTION: Critical public opinion, based on information that is made available to the public throughdifferent systems, has led companies that operate in the environment to continually improve their social, environmental, and ethical performance.OBJECTIVES: This paper aims to propose a fuzzy-logic-based model for the analysis of social corporate responsibility in cases of environmental accidents.METHODS: Our study employs techniques derived from social network analysis. The data was collected from the online database of The New York Times for the timespan from March 24, 1989, to September 1, 2017.RESULTS: The results show that the proposed model can be replicated, after some adjustments.CONCLUSION: We conclude that, despite the complexity of an analysis of this kind in which the model is applied considering isolated words in the text and not the semantic aspects, the proposed model based on fuzzy logic isadequate for the analysis of social corporate responsibility.
Keywords: fuzzy logic; fuzzy rules-based system; corporate social responsibility